KINEMATIC ANALYSIS OF GRINDULU FAULT IN PACITAN AND SURROUNDING AREA - GULTAF, HIKHMADHAN
Grindulu fault is one of active fault segments and pontential to produces earthquakes. Lineament of Grindulu Fault spread out from SW in Pacitan to NE in Tegalombo city. Paleostress and kinematic analysis of Grindulu Fault using stress inversion of fault slip data as main data. In this research, author using bouger anomaly data as secundary data to builds 3D top basement modelling covering research area and surorunding. The modelling data has purpose to interpreting structural lineament of top basement. Primary data consist of fault slip, fracture, fold, shear zone, surface lineament, bedding and description of lithology. Fault slip is a prime data to stress inversion analyzed that consist of strike and dip of fault surface data, also value of rake which showing sense of fault. Stress inversion using Right Dihedron Method and Rotational Oprimisation Method being developed by Delvaux and Sperner (2003) and using Win Tensor 4.0.4 was created and developed by Delvaux since year 2003 until present. The results of stress inversion showing five of maximum extension axes orientations (neotectonic deformation), that is: Phase 1 SSW – NNE; Phase 2 SW – NE; Phase 3 SWW - NEE; Phase 4 W – E; Phase 5 SEE – NWW. Grindulu Fault is left lateral stike – slip fault (sinistral) forms with W – E maximum extension axis orientation (Phase 4) in pure strike – slip with maximum shortening axis (P) is 49o/N016oE and maximum lenghtening asix is 07o/N275oE. Furthermore, iv changing of stress regime become transtensive stress regime with SEE – NWW maximum extension axis orientation (Phase 5). Present day, Grindulu Fault has left lateral and dip movement or left normal oblique strike – slip fault with transtensive stress regime. Occording to 3D top basement modelling, it is showing NE – SW lineaments as old pattern, in this case is Complex of Meratus Mountains. This pattern has also same to stike of Grindulu Fault. Thus, Grindulu Fault forms form reactivation of pre-existing NE – SW faults as old pattern in basement.